2008
DOI: 10.4319/lo.2008.53.6.2472
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between changing pCO2, N2 fixation, and Fe limitation in the marine unicellular cyanobacterium Crocosphaera

Abstract: We examined the physiological responses of steady-state iron (Fe)-replete and Fe-limited cultures of the biogeochemically critical marine unicellular diazotrophic cyanobacterium Crocosphaera at glacial (19 Pa; 190 ppm), current (39 Pa; 380 ppm), and projected year 2100 (76 Pa; 750 ppm) CO 2 levels. Rates of N 2 and CO 2 fixation and growth increased in step with increasing partial pressure of CO 2 (pCO 2 ), but only under Fe-replete conditions. N 2 and carbon fixation rates at 75 Pa CO 2 were 1.4-1.8-fold and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
144
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(161 citation statements)
references
References 55 publications
13
144
1
3
Order By: Relevance
“…It is widely distributed in tropical and subtropical waters (reported from the North and South Atlantic Ocean, North and South Pacific Ocean and the Arabian Sea), but reports on its physiology or ecology are still very recent (Falcó n et al, 2004(Falcó n et al, , 2005Tuit et al, 2004;Dyhrman and Haley, 2006;Zehr et al, 2007a;Fu et al, 2008;Compaoré and Stal, 2009;Hewson et al, 2009;Webb et al, 2009). The draft genome of C. watsonii WH 8501 is 6.24 Mb, with 323 contigs encoding a total of 5958 candidate protein-encoding genes (http://microbes.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely distributed in tropical and subtropical waters (reported from the North and South Atlantic Ocean, North and South Pacific Ocean and the Arabian Sea), but reports on its physiology or ecology are still very recent (Falcó n et al, 2004(Falcó n et al, , 2005Tuit et al, 2004;Dyhrman and Haley, 2006;Zehr et al, 2007a;Fu et al, 2008;Compaoré and Stal, 2009;Hewson et al, 2009;Webb et al, 2009). The draft genome of C. watsonii WH 8501 is 6.24 Mb, with 323 contigs encoding a total of 5958 candidate protein-encoding genes (http://microbes.…”
Section: Introductionmentioning
confidence: 99%
“…The process elucidated by the molecular-level measurements described here appears to be of global importance. With rising atmospheric CO 2 suggested to cause increases in marine nitrogen fixation (45), as well as a potential decrease in iron availability to marine phytoplankton in general (46), understanding the biochemical adaptations for iron scarcity in diazotrophs and their implications for marine primary productivity will be of increasing importance.…”
Section: Resultsmentioning
confidence: 99%
“…We expected to possibly see differences among the groups in responses to iron, because iron requirements may vary among diazotrophs and with environmental factors. It was recently shown that elevated CO 2 concentrations may reduce Fe requirements in Crocosphaera (Fu et al, 2008). UCYN-A does not have Photosystem II (Zehr et al, 2007a), which has three Fe atoms (Raven, 1990), thus it may require less iron than the photoautotrophic diazotrophs Crocosphaera and Trichodesmium.…”
Section: Responses In Unicellular Diazotrophsmentioning
confidence: 99%